THE RELATIONSHIP BETWEEN SEASON VARIATIONS AND DEPTH LEVEL ON THE GROWTH AND SURVIVAL RATE OF PEARL OYSTER SEEDS (Pinctada maxima) IN KAPONTORI BAY, BUTON ISLAND - M S Hamzah (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2014)
The pearl oyster (P. maxima) farming particularly in the Kapontori Bay, Buton Island waters and in other areas had complained for the mass mortality of pearl oysters saplings on the shell width between 3-4 cm. The mass mortality, was allegedly as a result of changing in environmental conditions and triggered by the shift in seasons. This research aimed to determine the effect of seasonal variations in water conditions at different depth levels on growth and survival of seedlings of pearl oysters conducted on March 27, 2007 to February 28, 2008. This research was very useful for pearl oyster farming in an effort to suppress the mass mortality rates based on the appropriate level of depth and seasons. The variance analyses showed that depth levels affected the survival rates of the pearl oyster seeds significantly (P<0.01). Based on honest significantly difference test, it also showed that the percentage number of survival rate was found higher within the depth of 2m (93.33%). Based on the relationship analyses between length and weight of shell body in all depths indicated a similar growth pattern of  minor allometric (b<3). The growth, survival rate, and environmental conditions based on depth levels on pearl oyster saplings were discussed in this paper. Keywords: Seasonal variation, survival rate, growth, pearl shell (P. maxima), depth level